Carbonic anhydrase IX-related tumoral hypoxia predicts worse prognosis in breast cancer: A systematic review and meta-analysis - Numprasit, Warapan; Yangngam, Supaporn; Prasopsiri, Jaturawitt; Quinn, Jean A.; Edwards, Joanne; Thuwajit, Chanitra (Frontiers in Medicine, 2023)
Background: tumoral hypoxia associated with aggressiveness of cancer including breast, however, the hypoxic measurement is intricate. Carbonic anhydrase 9 (CAIX) is a reliable endogenous hypoxic marker mainly depended on a master regulator of hypoxia called hypoxia-inducible factor-1α (HIF-1α). CAIX expression predicted poor prognosis in many solid malignancies, however, the role in breast cancer remains controversial. Methods: we performed a meta-analysis to evaluate the correlation of CAIX expression and disease-free survival (DFS) and overall survival (OS) in breast cancer. Results: a total of 2,120 papers from Embase, PubMed, Cochrane and Scopus were screened. Of these, 272 full texts were reviewed, and 27 papers were included in the meta-analysis. High CAIX was significantly associated with poor DFS (HR=1.70, 95% CI=1.39-2.07, p <0.00001) and OS (HR=2.02, 95% CI 1.40-2.91, p=0.0002) in breast cancer patients. According to breast cancer subtypes, the high CAIX group clearly associated with shorter DFS (HR=2.09, 95% CI =1.11-3.92, p=0.02) and OS (HR=2.50, 95% CI =1.53-4.07, p=0.0002) in TNBC; and shorter DFS in ER+ breast cancer (HR=1.81 95% CI =1.38-2.36, p<0.0001). Conclusions: high CAIX expression is a negative prognostic marker of breast cancer regardless of subtypes.